A CASE REPORT OF SUCCESSFUL TREATMENT OF STAGE IV ESOPHAGEAL CANCER - V. N. Khmelevskaya; P. A. Isaev; I. V. Gunko (Сибирский онкологический журнал)
Background. Esophageal cancer is among the ten most common cancers and causes-related mortality worldwide. Most patients present with an advanced stage tumor at diagnosis. To treat patients with esophageal cancer, radiation therapy in combination with chemotherapy is usually used. In the clinic of A.F. Tsyb Medical Radiological Scientific Center, patients with advanced esophageal cancer are treated with split-course radiotherapy delivered in two fractions (1–1.5 Gy) with a 4-hour interval. The positive effect is observed significantly earlier than in conventional radiotherapy.Case description. A 50-year-old male patient presented with complaints of hoarseness of voice and difficulty swallowing in February 2015. The patient was diagnosed with stage cТ4N2M1 cervical esophageal cancer (tumor length 3.5 cm) with metastases in cervical lymph nodes and the thyroid and esophageal stenosis (stage IV). Cytological examination revealed keratinizing squamous cell esophageal carcinoma. The tumor was considered inoperable. The patient underwent gastrostomy. Radiation therapy delivered to the tumor and metastases was performed 5 times a week using two lateral fields and one anterior field. The total radiation dose was 60 Gy. A complete response was achieved. Three courses of chemotherapy with carboplatin (AUC 6), paclitaxel (75 mg/m2 ) with a 21-day interval were administered 2 months after radiotherapy. In January 2016, new metastases in the thyroid were detected. Thyroidectomy with microsurgical neurolysis of the laryngeal nerves was performed. The patient is alive 3 years and 7 months after diagnosis.Conclusion. The use of nonconventional fractionated radiotherapy schedules in combination with chemotherapy allows satisfactory treatment outcomes in patients with advanced esophageal cancer to be obtained.